THE EFFECT OF USING E-LEARNING TOOLS BASED ON VISUALIZATION IN TEACHING AND LEARNING LATIN - Balalaieva, Olena (Revista Conhecimento Online: Diversidade e Inclusão Social, 2020)
ABSTRACT: The article deals with the problem of using visualization in teaching and learning Latin. Both positive and negative implementation aspects of a classic didactic principle of visualization are analyzed in terms of e-learning. The experimental research aimed to carry out the system of pedagogical impact by means of e-learning tools based on visualization and evaluate the effect of using such tools on teaching and learning Latin. The ways to minimize didactic risks that may result from inappropriate (from psychological and educational points of view) use of visual aids in e-learning tools are outlined. The necessity to keep up with the demand for reasonable visualization sufficiency is shown. The pedagogical experiment has proved the advantage using of e-learning tools based on visualization in learning Latin by following criteria: motivation (indicators: focus and level of academic motivation), cognition (indicators: quality and amount of knowledge, academic performance), activity (indicators: mastering practical skills, speed of execution of training tasks). The results of the pedagogical experiment (including the comparison of the results of the experimental and control groups) give the grounds to state that training veterinary students with using e-learning tools based on visualization is more effective than the traditional one. Keywords: Visualization. E-learning tools. Professional training. Latin. RESUMO: O artigo trata do problema de usar a visualização no ensino e aprendizagem de latim. Aspectos de implementação positivos e negativos de um princípio didático clássico de visualização são analisados em termos de e-learning. A pesquisa experimental teve como objetivo realizar o sistema de impacto pedagógico por meio de ferramentas de e-learning baseadas na visualização e avaliar o efeito do uso de tais ferramentas no ensino e aprendizagem do latim. São descritas as maneiras de minimizar os riscos didáticos que podem resultar do uso inadequado (do ponto de vista psicológico e educacional) de recursos visuais nas ferramentas de e-learning. A necessidade de acompanhar a demanda por suficiência razoável de visualização é mostrada. O experimento pedagógico demonstrou a vantagem do uso de ferramentas de e-learning baseadas na visualização no aprendizado de latim, mediante os seguintes critérios: motivação (indicadores: foco e nível de motivação acadêmica), cognição (indicadores: qualidade e quantidade de conhecimento, desempenho acadêmico), atividade (indicadores: domínio das habilidades práticas, velocidade de execução das tarefas de treinamento). Os resultados do experimento pedagógico (incluindo a comparação dos resultados dos grupos experimental e controle) fundamentam a afirmação de que o treinamento de estudantes de veterinária com o uso de ferramentas de e-learning baseadas na visualização é mais eficaz do que o tradicional. Palavras-chave: Visualização. Ferramentas de e-learning. Treinamento profissional. Latim.